PERAN INDEKS MASSA TUBUH TERHADAP KADAR TESTOSTERON PADA PRIA DIABETES MELITUS TIPE 2 DENGAN TERAPI METFORMIN - Sabrina, Maiyeni; Lukas, Stefanus (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
Type 2 diabetes mellitus (T2DM) is a metabolic disorder often accompanied by decreased testosterone levels in men. Metformin is effective in lowering blood glucose, but its impact on testosterone remains controversial.To evaluate the effects of metformin dose, age, and changes in body mass index (BMI) on testosterone levels in men with T2DM. A pre–post study was conducted on 79 male T2DM patients receiving metformin. Data included metformin dose, age, BMI, and testosterone levels before and after therapy. Spearman correlation and multiple linear regression were used for analysis. Changes in BMI showed a strong correlation (ρ = 0.608; p = 0.000) and metformin dose showed a moderate correlation (ρ = 0.564; p = 0.000) with changes in testosterone. Regression analysis identified BMI as the dominant factor (β = 0.523; p = 0.009), while age was not significant (p > 0.05). This study provides simultaneous analysis of metformin dose, BMI, and age using a pre–post design. A unique finding was that BMI reduction was followed by decreased testosterone levels, contrasting with most international studies. Changes in BMI were the most dominant factor influencing testosterone levels in men with T2DM receiving metformin.